2016
DOI: 10.3390/ijerph13060543
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relationship between Estradiol and Follicle-Stimulating Hormone Concentrations and Polymorphisms of Apolipoprotein E and LeptinGenes in Women Post-Menopause

Abstract: Background: Menopause is the permanent cessation of menstruation due to loss of ovarian follicular activity. A review of the available literature indicates that correlations between the changes that take place in a woman’s body after menopause and different genetic variants are still being sought. Methods: The study was conducted in 252 women who had completed physiological menopause. The women were divided into groups according to the time elapsed since menopause. The total concentrations of estradiol and fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…serum concentrations than the other five genotypes (Ryl et al, 2016), while another study found that the presence of at least one ε2 allele is associated with later menopause than ε3/ε3 (Tempfer et al, 2005). Early menopause is thought to be linked to increased LOAD risk due to reduced life-long exposure to estrogen (Gilsanz et al, 2019).…”
Section: Apoe and Sex Hormonesmentioning
confidence: 99%
“…serum concentrations than the other five genotypes (Ryl et al, 2016), while another study found that the presence of at least one ε2 allele is associated with later menopause than ε3/ε3 (Tempfer et al, 2005). Early menopause is thought to be linked to increased LOAD risk due to reduced life-long exposure to estrogen (Gilsanz et al, 2019).…”
Section: Apoe and Sex Hormonesmentioning
confidence: 99%